2013
DOI: 10.1371/journal.pone.0062573
|View full text |Cite
|
Sign up to set email alerts
|

Sponge Communities on Caribbean Coral Reefs Are Structured by Factors That Are Top-Down, Not Bottom-Up

Abstract: Caribbean coral reefs have been transformed in the past few decades with the demise of reef-building corals, and sponges are now the dominant habitat-forming organisms on most reefs. Competing hypotheses propose that sponge communities are controlled primarily by predatory fishes (top-down) or by the availability of picoplankton to suspension-feeding sponges (bottom-up). We tested these hypotheses on Conch Reef, off Key Largo, Florida, by placing sponges inside and outside predator-excluding cages at sites wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
116
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(124 citation statements)
references
References 55 publications
2
116
1
2
Order By: Relevance
“…Tests of resource allocation theory at the community or ecosystem levels have been hampered by the complexity of most food webs and the interactions of top-down and bottom-up effects (21). The community of sponges on Caribbean coral reefs provides a simpler system for testing resource allocation theory across a large biogeographic region, perhaps because of the relative lack of bottom-up effects (9). Although previous research revealed the existence of top-down control and resource trade-offs using experimental manipulations with individual sponge species (9,(12)(13)(14), this study demonstrates that interspecific differences in sponge chemical defenses correlate with community-level differences in sponge community structure that can be detected across a large biogeographic region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tests of resource allocation theory at the community or ecosystem levels have been hampered by the complexity of most food webs and the interactions of top-down and bottom-up effects (21). The community of sponges on Caribbean coral reefs provides a simpler system for testing resource allocation theory across a large biogeographic region, perhaps because of the relative lack of bottom-up effects (9). Although previous research revealed the existence of top-down control and resource trade-offs using experimental manipulations with individual sponge species (9,(12)(13)(14), this study demonstrates that interspecific differences in sponge chemical defenses correlate with community-level differences in sponge community structure that can be detected across a large biogeographic region.…”
Section: Discussionmentioning
confidence: 99%
“…Although sponges are generally thought to feed by capturing particles, they may also absorb dissolved organic material directly from the seawater they pump through their bodies (7,8). This feeding versatility may help explain why the bottomup effects of particulate food availability on sponge growth appear to be negligible, suggesting that sponge communities are primarily structured by top-down factors (9). Although many Caribbean sponge species are chemically defended by secondary metabolites that include alkaloids, terpenoids, and glycosides (10), other species are palatable to sponge predators (9,11), revealing a resource trade-off between the production and maintenance of chemical defenses versus other life functions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Caribbean reefs sponge assemblages have been found to be primarily controlled by predatory reef fishes (Pawlik et al, 2013) and by hawksbill turtles (Pawlik et al, 2018). The biodiversity and abundance of spongivorous fishes and sponges in Caribbean reefs are considerably higher than in Southwestern Atlantic reefs (Roberts et al, 2002;van Soest et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Evidences in high diversity coral reefs, such as Caribbean reefs, showed that top-down regulation by fish play a decisive role on growth of different sponge species, consequently affecting benthic assemblages (Dunlap and Pawlik, 1996;Pawlik, 1997Pawlik, , 1998Pawlik et al, 2013Pawlik et al, , 2018. Brazilian coral reefs have peculiar features as relatively low coral diversity, high sedimentation rates and elevated turbidity due to abundant river flow into shore.…”
Section: Introductionmentioning
confidence: 99%